(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Organizations' competitive advantage increasingly depends on effective knowledge management and organizational learning. Successfully implementing knowledge management systems depends on employee behavior especially on knowledge sharing among employees. The main purpose of this paper is to assess the personal factors that affect knowledge sharing behavior among academic staff at the University of Kigali, Rwanda. This research paper is based on the theory of perceived behavior. Research data collected from fourteen full-time staff of the University of Kigali using printed questionnaires. It was observed that the academic staff at the University of Kigali share knowledge acknowledged that sharing knowledge is a good and pleasant thing, and they share knowledge to acquire new knowledge and experiences. They further indicated that they believe that sharing new ideas will save time, and it is within their control. Moreover, the academic staff noted that they share knowledge for the sake of their colleagues regardless of the colleague’s level of knowledge and experience. However, it can be observed that most academic staff feels that they share more knowledge with their colleagues than they receive from their colleagues.